Measuring the aggregated impact of research: Establishing criteria for coding Translational Science Benefits Model data - Nicole Miovsky; Amanda Woodworth; Stephanie Andersen; Rosalina Das; Julie Heidbreder; Rechelle Paranal; Clara M. Pelfrey; Jessica Sperling; Beth Tigges; Boris B. Volkov; Margaret Schneider (Journal of Clinical and Translational Science)
Abstract